Law, history, the Low Countries, and Europe - Caenegem, R. C. van (Hambledon Press, 1994)
R.C. Van Caenegem is the successor of Henri Pirenne and of F.L. Ganshof at the University of Ghent. These essays reflect Van Caenegem's main interests over his career: the Common Law in England and Customary Law in the Low Countries; the differences between institutional development in England and in the rest of Europe; and the forces making for autocratic as opposed to representative government. A number of pieces discuss the nature of history itself: how it compares with the sciences and what it can teach us. Two essays commemorate the lives and work of Pirenne and Ganshof.